De l’indépendance politique à l’émancipation culturelle:le rôle de la diplomatie latino-américaine en Europe - Enrique Sánchez Albarracín (Les Cahiers ALHIM)
The Latin American republics were built in the margins of Europe, as part of a long history of emancipation that far exceeds the time limits proclamations of independence. The Latin American diplomats have often played a decisive role in this process, working first at the geographical and legal recognition of new nation states, then promote the integration of regional economies on international markets and seeking to create, ultimately, recognition of cultural and intellectual legitimacy of Latin America in the world. It is this latter attitude that we see here, trying to show how it fits into paradoxical and hybrid history, derived from the settlement and its subsequent collective representations. Diplomacy is not only the art of negotiation, it is also the art of representation, seduction. The goal for these emissaries of independent America, was first a reversal of perspective: ensuring that the new Latin American nations are no longer seen as objects but subjects of world history ; act on the representations and advocate for genuine reciprocity, while affirming a reappropriation of their geographical and cultural.